legal Basis for the Crime of Electronic Extortion of Children Through social media and Its Protected Interest (Journal of Misan Researches, 2022)
Children are now vulnerable to electronic crimes because of the wrong use of modern means of communication and their inability to tackle these media social media have become increasingly common in all walks of life, especially after the year 2003 when Iraq entered the use of modern technology in communicationAlthough useful social media have impacted our society religious social culturally and economically electronic crimes have widely spread in our society as a result of the wide use of electronic equipment and the internet electronic blackmail of children through social media has increased their friend our social psychology and socially blackmailing means threatening the victim, especially children by the blackmail er to cause material and emotional harm to the victim or to another person related to the victim to carry out legal or illegal activities for one reason or another.